Development of peanut varieties with high oil content by in vitro mutagenesis and screening - Jing-shan WANG; Lei SHI; Yue LIU; Ming-xia ZHAO; Xia WANG; Li-xian QIAO; Jiong-ming SUI; Guan LI; Hong ZHU; Shan-lin YU (Journal of Integrative Agriculture, 2020)
Peanut (Arachis hypogaea L.) is an important oil crop globally and high oil content is one of the major targets in peanut breeding programs. Previous studies indicated that the osmotic pressure (OP) of the leaves of peanut plants subjected to drought stress was negatively correlated with kernel oil content. Based on this knowledge, we established a practical and reliable method for creating new peanut varieties with high oil content using in vitro mutagenesis and directional OP-based selection. Using embryonic leaflets of peanut variety Huayu 20 as explants, pingyangmycin (PYM) as the mutagen, and hydroxyproline (HYP) as the OP regulator, we developed 15 HYP-tolerant regenerated plants. For each regenerated plant, we selected offspring with oil content>55% (relative to 49.5% for Huayu 20). We developed and released three new peanut varieties with high yield and high oil content from the offspring of the HYP-tolerant regenerated plants. The three new varieties were named as Yuhua 4, Yuhua 9 and Yuhua 14 and their oil contents were 57.7, 61.1 and 59.3%, respectively. The results indicate that in vitro mutagenesis with PYM followed by directed screening with HYP is a useful approach for breeding peanut varieties with high oil contents.